2014
DOI: 10.1149/06127.0019ecst
|View full text |Cite
|
Sign up to set email alerts
|

(De)lithiation-Induced Phase Transitions of LiMTiO4 Spinels

Abstract: Nanocrystalline LiMn 3+ TiO 4 (~10 nm, annealed in air at 500°C) and LiFe 3+ TiO 4 (3~5 nm, annealed in argon at 600°C) were synthesized by a sol-gel route, and their structural changes upon Li + extraction and reinsertion were investigated. To determine accurately the phase compositions of the nanosized materials, we used combined techniques of X-ray diffraction (XRD) Rietveld refinement and synchrotron pair distribution function (PDF) analysis. Partial lithium from LiMTiO 4 (M = Mn, Fe) can be extracted on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…41,42 Furthermore, we confirmed that the crystal structure of the electrochemically generated Li 1.93 FeTiO 4 is different from that of chemically prepared Li 2 FeTiO 4 (Fm% 3m). 43,44 In addition, the lithiation voltage for the spinel LiFeTiO 4 is about 0.2 V higher than that for the chemically synthesized rock-salt Li 2 FeTiO 4 (B2.4 V). 43 These results indicate a small effect of Li + insertion/extraction on the spinel host framework and thus a single-phase and quasi zero-strain lithiation/delithiation behaviour.…”
Section: Fe Mo ¨Ssbauer Spectramentioning
confidence: 99%
“…41,42 Furthermore, we confirmed that the crystal structure of the electrochemically generated Li 1.93 FeTiO 4 is different from that of chemically prepared Li 2 FeTiO 4 (Fm% 3m). 43,44 In addition, the lithiation voltage for the spinel LiFeTiO 4 is about 0.2 V higher than that for the chemically synthesized rock-salt Li 2 FeTiO 4 (B2.4 V). 43 These results indicate a small effect of Li + insertion/extraction on the spinel host framework and thus a single-phase and quasi zero-strain lithiation/delithiation behaviour.…”
Section: Fe Mo ¨Ssbauer Spectramentioning
confidence: 99%